Possible Impact of Boreal Winter Siberian High on ENSO Development in the Following Year - Fu, Jiayu; Liu, Minghong; Wang, Run; Wang, Yuwen; Zhao, Shuo (Frontiers in Earth Science, 2022)
The Siberian High (SH) is the dominant pressure system located in the mid- to high- latitudes of Eurasia during the boreal wintertime. In this paper, we reveal a triggering impact of the SH variation in the preceding winter on the following ENSO events and give a possible explanation via diagnosing the evolution of the SH-associated response over the tropical Pacific and North Pacific. When the SH is anomalously enhanced (suppressed) during the boreal winter, a synchronized Aleutian Low enhanced (suppressed) response will occur over the downstream North Pacific and gradually evolve into a meridional dipole structure similar to the negative (positive) phase of the North Pacific Oscillation (NPO) during the following spring and early summer. Corresponding to the NPO-like circulation, the oceanic response in the North Pacific features a pattern similar to the negative (positive) phase of the Victoria mode. These SH-associated atmospheric and oceanic anomalies over the subtropical North Pacific will be maintained and further delivered into the tropical Pacific through the so-called seasonal footprinting mechanism, favoring the Bjerknes feedback established around boreal summer and finally growing into a La Niña (El Niño) in the following winter.